Developing a Differential Zone for Virus Disease Prevention using Phytoterapy - Mukhina A. A. (Science, education, society: trends and prospects, 2020)
Pulmonology is a branch of medicine that treats diseases of the respiratory system. An important problem in the modern world is chronic obstructive pulmonary diseases: bronchial asthma, emphysema, chronic bronchitis, including obstructive and others. This group of diseases with a transient or permanent violation of airway patency with the development and further progression of respiratory failure.
Keywords: болезни органов дыхания; санаторно-курортное лечение; diseases of the respiratory system; Spa treatment; фитонцидные растения; оздоровительная профилактика; phytoncide plants; health prevention